2013
DOI: 10.1590/1414-431x20133117
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of aging on spatial contrast sensitivity to linear and polar sine-wave gratings

Abstract: Changes in visual function beyond high-contrast acuity are known to take place during normal aging. We determined whether sensitivity to linear sine-wave gratings and to an elementary stimulus preferentially processed in extrastriate areas could be distinctively affected by aging. We measured spatial contrast sensitivity twice for concentric polar (Bessel) and vertical linear gratings of 0.6, 2.5, 5, and 20 cycles per degree (cpd) in two age groups (20-30 and 60-70 years). All participants were free of identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
5
0
2
Order By: Relevance
“…A decrease in binocular summation ratio with ageing for CM letters in older adults may reflect an early decline in higher visual areas, most likely higher than V1. This speculation is supported by the study of Costa et al (2013) which suggested that ageing might have a more pronounced effect in higher visual areas than in the primary striate cortex. It is vital to know what biological (e.g.…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…A decrease in binocular summation ratio with ageing for CM letters in older adults may reflect an early decline in higher visual areas, most likely higher than V1. This speculation is supported by the study of Costa et al (2013) which suggested that ageing might have a more pronounced effect in higher visual areas than in the primary striate cortex. It is vital to know what biological (e.g.…”
Section: Conclusion and Discussionmentioning
confidence: 78%
“…Dorr et al found a similar shape to these app results for the CSF determined using a 2‐AFC procedure on both the iPad and a traditional CRT laboratory setup, with no ‘peaks’ seen but with a maximum contrast sensitivity around 1.0 cpd. Also previous studies using research laboratory grade CRT setups found maximum contrast sensitivities to occur between 2.0 to 5.0 cpd . Artefacts or visual cues present within the CSV‐1000 printed chart may bias patient responses and explain why peak contrast sensitivity appears to be shifted towards the higher frequencies.…”
Section: Discussionmentioning
confidence: 90%
“…Also previous studies using research laboratory grade CRT setups found maximum contrast sensitivities to occur between 2.0 to 5.0 cpd. [24][25][26] Artefacts or visual cues present within the CSV-1000 printed chart may bias patient responses and explain why peak contrast sensitivity appears to be shifted towards the higher frequencies. The difference in sensitivity between the apps and the Pelli-Robson chart is unsurprising as the apps are specified in 27,28 and none of these used a chart of similar design allowing comparison of the thresholds across the range of spatial frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Esses resultados corroboram com outros dados da literatura, mesmo apresentando métodos diferenciados (Burton et al, 1993;Costa et al, 2013;Costa et al, 2009;McGrath & Morrison, 1981;Skalka, 1980). Burton et al (1993) verificou monocularmente a SC de adultos jovens (17-29 anos) e idosos (60-80 anos) por meio do paradigma dos estímulos constantes e percebeu uma diminuição no contraste visual para frequências de 2, 4, 8, 12, 16, 24, 28 e 32 cpg.…”
Section: Discussionunclassified
“…Pesquisas relacionadas a percepção visual mostram que curvas de SC podem ser bastante úteis na detecção de simples padrões visuais em forma de ondas senoidais espaciais com orientação vertical e horizontal (Kalia et al, 2012;Jia, Yan, Hou, Lu & Huang, 2014;Lesmes, Jackson, Wallis, Bex, 2013;Scialfa, Kline & Wood, 2002;Skalka, 1980;Pelli & Bex, 2013). Esses diferentes padrões comportamentais distinguem maneiras dos mecanismos neurais processarem a informação (Costa et al, 2013;Ellemberg, Lewis, Hong Liu, & Maurer, 1999;Santos, Oliveira, Nogueira, Cruz, & Simas, 2006). Neste sentido, este estudo teve por objetivo avaliar a curva de SC de adultos e idosos saudáveis para estímulos de grades senoidais verticais utilizando frequências de 0,6; 2,5; 5 e 20 cpg em condições de luminância fotópica.…”
unclassified